2023
DOI: 10.1097/cm9.0000000000002178
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol attenuates mitochondrial fission and cell apoptosis by activating Sirt3 in intracerebral hemorrhage

Abstract: Background: Sirtuin-3 (Sirt3) has been documented to protect against mitochondrial dysfunction and apoptosis. Honokiol (HKL) is a Sirt3 pharmacological activator with reported neuroprotective effects in multiple neurological disorders. The present study aimed to explore the neuroprotective effects of HKL and the role of Sirt3 following intracerebral hemorrhage (ICH). Methods: An in vivo ICH model in rats was established by injecting autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous studies have found that SIRT3 plays a significant role in improving apoptosis and mitochondrial fission, and similarly, SIRT1 also plays an important role in oxidative stress and apoptosis. [ 38 ] Our results show that electroacupuncture intervention increased protein and mRNA expression of SIRT-1 and PGC-1α in mTBI rats.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have found that SIRT3 plays a significant role in improving apoptosis and mitochondrial fission, and similarly, SIRT1 also plays an important role in oxidative stress and apoptosis. [ 38 ] Our results show that electroacupuncture intervention increased protein and mRNA expression of SIRT-1 and PGC-1α in mTBI rats.…”
Section: Discussionmentioning
confidence: 76%